Brain tumor-associated epilepsies in adulthood: Current state of diagnostic and individual treatment options - Stefan, Hermann; Bösebeck, Frank; Rössler, Karl (Seizure-European Journal of Epilepsy, 2024)
Brain tumors are one of the most frequent causes of structural epilepsy and set a major burden on treatment costs and the social integrity of patients. Although promising oncological treatment strategies are already available, epileptological treatment is often intractable and requires lifelong epileptological care. Therefore, treatment strategies must be adapted to age-related needs, and specific aspects of late-onset epilepsy (LOE) must be considered. The practical implementation of individual decisions from tumor boards and the current state of the art in scientific knowledge about pathological mechanisms, modern diagnostic procedures and biomarkers, and patient-individualized treatment options into practical epileptological disease management is a prerequisite. This narrative review focuses on the current work progress regarding pathogenesis, diagnosis, and therapy. Exemplarily, interdisciplinary approaches for optimized individualized therapy will be discussed, emphasizing the combination of neurological-epileptological and oncological perspectives.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Genetic treatment; Histo-molecular classification; Late-onset epilepsy; Neurotransmitter; Prognosis; Tumor epilepsy